2022
DOI: 10.3389/fsurg.2022.852906
|View full text |Cite
|
Sign up to set email alerts
|

Can the Ratio SUVmax of the Lesion/SUVmax of Mediastinal Tissues Guide the Choice of Surgical Access for the Resection of Thymic Epithelial Tumors?

Abstract: BackgroundThere are studies showing the utility of the 18-fluorodeoxyglucose positron emission tomography (18FDG PET) scan in the management of patients with thymic epithelial tumors. It seems to be a correlation between the standard uptake value (SUVmax) of thymic epithelial tumors and the histological type and the stage. This study aims to use the ratio of the SUVmax of the lesion to the SUVmax of the adjacent mediastinal tissues in order to guide the choice of the surgical access.MethodsAll patients who pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… 46 In a study which enrolled 30 patients more advanced Masaoka‐Koga stages were observed (without reaching statistical significance) and the capsular invasion was significantly higher when the SUVmax ratio was superior to 1. 46 …”
Section: Methods ‐ Search Strategymentioning
confidence: 99%
See 3 more Smart Citations
“… 46 In a study which enrolled 30 patients more advanced Masaoka‐Koga stages were observed (without reaching statistical significance) and the capsular invasion was significantly higher when the SUVmax ratio was superior to 1. 46 …”
Section: Methods ‐ Search Strategymentioning
confidence: 99%
“…There appears to be a correlation between the standard uptake value (SUVmax) of TET and the histological type according to the WHO classification and the stage according to the Masaoka‐Koga classification 14,46 . Thymic carcinomas can be distinguished from thymomas because of a significantly higher SUVmax.…”
Section: Methods ‐ Search Strategymentioning
confidence: 99%
See 2 more Smart Citations